1980
DOI: 10.3189/s0022143000010364
|View full text |Cite
|
Sign up to set email alerts
|

Does the Permanent Creep-Rate of Polycrystalline Ice Increase with Crystal Size?

Abstract: ABSTRACT. Uniaxial compression creep tests were p erformed on a rtificial and natural polycrystalline ices at tempera tures near -7°C . The grain-size range investigated was from I to 10 mm. C ontrary to previous results, the p ermanent creep-ra te was not found to in crease with crystal size. Only the transien' t creep appears to b e sensitive to variations in crystal size.R EsuME . L a vitesse du j1uage stationnaire de la glace poiyeristalline erolt elle avee la taille des eristaux? Des experiences d e fluag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Grain-size effects, on the other hand, have received comparatively little attention. A number of papers have appeared in the literature that deal with grain-size effects on compressive creep of ice (Baker, 1978;Duval and Le Gac, 1980;Jones and Chew, 1983;Jacka, 1984;Jacka and Maccagnan, 1984). On balance, the results indicate that, while grain-size has an influence on primary creep rates, the minimum creep rate and subsequent tertiary creep appear to be unaffected by the initial grain-size of the material.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Grain-size effects, on the other hand, have received comparatively little attention. A number of papers have appeared in the literature that deal with grain-size effects on compressive creep of ice (Baker, 1978;Duval and Le Gac, 1980;Jones and Chew, 1983;Jacka, 1984;Jacka and Maccagnan, 1984). On balance, the results indicate that, while grain-size has an influence on primary creep rates, the minimum creep rate and subsequent tertiary creep appear to be unaffected by the initial grain-size of the material.…”
Section: Introductionmentioning
confidence: 85%
“…This behavior results from the fact that the coarsegrained material undergoes the transition to brittle behavior at lower strain-rates than does the fine-grained material. Other work (Duval and Le Gac, 1980;Mellor and Cole, 1982) has clearly indicated that under compressive loading the minimum strain-rate in creep tests and the peak stress in strength tests on ice occur at a relatively constant axial strain level of 0.0 I. However, it is apparent from the present work and from the results of creep tests on identical material (Cole, 1986) that the strain at either the peak stress or the minimum creep rate should be considered as a function of grain-size under certain conditions .…”
Section: Additional Discussionmentioning
confidence: 99%
“…I did not do that here since the grain size that was used was fairly uniform and deformation of ice under the conditions modeled does not show a strong dependence on grain size [Duval and LeGac, 1980]. However, grain size may be important when mechanisms other than intracrystalline slip contribute to the deformation [Goldsby and Kohlstedt, 1996;Cuffey et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Explanations for this grain-growth reduction have been discussed for many years (e.g. Gow and Williamson, 1976;Duval and Gac, 1980;Paterson, 1994), but there is, as yet, no consistent understanding to be found in the literature. In laboratory ice deformation experiments Jacka and Li (1994) found a steady-state crystal size with the tertiary creep stage.…”
Section: Introductionmentioning
confidence: 99%